Hydrothermal Synthesis and Crystal Structure of Ni(II) Complex with Azamacrocycle - Bi, Jian-Hong; Li, Meng; Dong, Hua-Ze (Asian Journal of Chemistry, 2015)
A new azamacrocyclic Ni(II) complex with the m.f. C24H44N8O2Ni2 was synthesized by hydrothermal reaction and characterized by IR spectra and single-crystal X-ray diffraction. The crystal is in a Triclinic system, space group P-1 with unit cell parameters: a = 9.4238(3)Å, b = 9.44760(10) Å, c = 9.5006(3)Å, a = 77.706(2)º, b = 65.597(2)º, g = 71.132(2)º, V = 725.81(3)Å3, Z = 1, Mr = 594.09, Dc = 1.359 Mg/cm3, μ = 1.332 mm-1, F(000) = 316, T = 298(2) K, R = 0.0621, wR = 0.1534 for 3825 reflections with I > 2s(I). The crystal structure analysis shows that the nickel(II) ion was coordinated by four nitrogen atoms of the azamacrocycle.